(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
The years of the 1950’s are one of the most turbulent time in hungarian history, which caused serious damage in the society’s structure. We have to discuss these problems to elaborate the past and revaluate the present. The research’s main question is that how the children affected by the rearrangment of the hungarian educational system influenced by the Soviet Union. Did they recognise the importance of the changes, even notice the positive or negative part of them? We must know our past to understand our present. I want to support this statement with my research. as I do oral history interviews with the witnesses of our history. The goal is to make a free narrative interview, where I can get the answers to my questions from those, who lived through the years of the 1950’s. The interviews made so far are not allow to jump to significant conclusions yet, but we could see the different impact it made to different social classes.